Multi-societal expert consensus statement on the safe administration of ultrasound contrast agents - Jordan B. Strom; Andrew Appis; Richard G. Barr; Maria Cristina Chammas; Dirk-André Clevert; Kassa Darge; Linda Feinstein; Steven B. Feinstein; J. Brian Fowlkes; Beverly Gorman; Pintong Huang; Yuko Kono; et al. (Echo Research and Practice)
Abstract Contrast enhanced ultrasound (CEUS) offers a safe, reliable imaging option to establish a clinical diagnosis across a variety of multidisciplinary settings. This Expert Consensus Statement serves to outline expert opinion on what constitutes appropriate supervision and the essential components of safe CEUS practice. The purpose of this document is to empower institutions to allow sonographers, along with other trained medical professionals, to administer UCAs at the point of care, consistent with the updated scope of practice documentation and within the broad parameters of an individual’s training and licensure, while subject to appropriate supervision and meeting or exceeding minimum safety standards. This guidance was developed by the International Contrast Ultrasound Society and endorsed by the following organizations that represent ultrasound professionals: the British Society of Echocardiography, the Canadian Society of Echocardiography, the Society of Diagnostic Medical Sonography, the Society for Pediatric Radiology, the World Federation of Ultrasound in Medicine and Biology, the Brazilian College of Radiology, the Joint Review Committee for Diagnostic Medical Sonography, the Chinese Ultrasound Doctors Association, and the American Society of Neuroimaging. Additionally, this guidance document was affirmed or supported by the American Society of Echocardiography, the Association for Medical Ultrasound, and the Society for Vascular Ultrasound.